Improvement in the Properties of Soil using Fly Ash and Coir Fibre (International Journal of Innovative Research in Engineering & Management, 2022)
The reliability and strength of the ground  assume a very important role in the field of development  advancement. Different changing procedures can be  adopted for the floor which needs enough firmness. The  change can increase the shear strength of the soil and  control the increase in soil properties, thus improving the  load limit of the subgrade pile to help asphalts and  installations. There is a gigantic variety of change  techniques. The convergence point of this report is to focus  on the common sense of settling the soil through the use of  rubble and coir, thus reusing waste materials and providing  a productive and ecological procedure for soil change or  adjustment.
Keywords: Fly ash; Coir fibre; Optimum moisture